CONCEPT OF AUTOMATED CONTROL SYSTEM WITH ANALYZING CONDITION OF THE ERGATIC COMPONENT - Blahaia, Ludmila; Polishchuk, Sergey (Proceedings of National Aviation University (archive), 2014)
In this work the automated control system structure and configuration together with the mathematicaldescription of the person-operator are considered in details. The proposed concept of human-operator organismrepresentation as an ergatic object gives the possibility to provide mathematical approach to the description of the ACSwith the prognostication of human-operator cybernetic ability. It will allow to solve problems of a human factor inmodern conditions of aircraft control.